2019
DOI: 10.1177/1545968319856893
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior and Quality of Life in Individuals With Parkinson’s Disease

Abstract: Background. Sedentary behavior is a growing public health concern and may have particular relevance for the Parkinson disease (PD) population. However, the influence of sedentary time on factors associated with quality of life (QOL) in PD is unknown. The primary purpose of this study was to examine relationships between sedentary behaviors and markers of PD-specific QOL. A secondary purpose was to examine relationships between physical activity behaviors and QOL. Methods. We assessed sedentary and active behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 36 publications
1
49
0
4
Order By: Relevance
“…Although this group spent time in LIPA in the morning, this activity drops steadily from midday onwards, explaining a total activity count that is 75% lower than "Steady Movers". It is previously reported that prolonged bouts of SB appear characteristic of more advanced PD compared to controls [37] and these uninterrupted bouts also appear more strongly associated with quality of life in this group [38]. A feasible starting point for PA promotion for this group, could be to break up bouts of prolonged sitting in the afternoon and evening time.…”
Section: Discussionmentioning
confidence: 87%
“…Although this group spent time in LIPA in the morning, this activity drops steadily from midday onwards, explaining a total activity count that is 75% lower than "Steady Movers". It is previously reported that prolonged bouts of SB appear characteristic of more advanced PD compared to controls [37] and these uninterrupted bouts also appear more strongly associated with quality of life in this group [38]. A feasible starting point for PA promotion for this group, could be to break up bouts of prolonged sitting in the afternoon and evening time.…”
Section: Discussionmentioning
confidence: 87%
“…A total of 24,959 (range: 23 to 3749) community-dwelling older adults were included with mean or median age ranging from 60.0 to 92.3 years and, on average, populations were 54.6% female. In 11 articles, specific disease groups were studied: osteoarthritis (OA), 34 , 36 , 44 , 54 chronic obstructive pulmonary disease (COPD), 28 , 39 , 45 , 56 cirrhosis, 37 Parkinson’s disease, 38 and stroke survivors. 40 Longitudinal associations were reported in six articles 27 , 31 , 34 , 36 , 53 , 54 (mean follow-up period of 3.1 years) and represented 7554 older adults with mean or median age ranging from 62.4 to 80.6 years (56.8% female); remaining articles reported cross-sectional associations ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accelerometers were used in 28 studies, while two studies 27 , 28 used pedometers to objectively measure PA/SB ( Table 3 ). The following measures of PA/SB were included: number of steps (or walking duration), 27 , 28 , 37 , 38 , 41 , 44 , 45 , 50 , 55 activity counts (or accelerations, movement intensity), 29 , 33 , 42 , 43 , 45 , 49 , 53 , 55 , 56 energy expenditure (EE), 31 , 37 , 45 , 50 duration (in different units of time) of total PA (TPA) (or mobile duration), 45 , 47 , 51 , 56 moderate to vigorous PA (MVPA) (or moderate PA (MPA) or vigorous PA (VPA) individual), 30–32 , 34 , 36–40 , 46–49 , 51 , 52 , 54 , 55 light PA (LPA), 34 , 40 , 47 , 49 , 52 , 55 and SB (or lying duration, immobile time), 30–32 , 35 , 37 , 38 , 40 , 43 , 45 , 47 , 49 , 52 , 55 breaks per sedentary hour (SB break rate), 52 and breaks in sedentary time (BST). 32 , 52 , 55 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, using the present design, we managed to explore the differences between a widely used training method (FW) and a new method (NW). We aimed to perform a clinical trial testing the superiority of a relatively new endurance modality (NW) against a well-known endurance activity (FW) that has already shown positive results in the literature [ 28 , 29 , 30 ]. Third, the limitations include the short time of the intervention.…”
Section: Discussionmentioning
confidence: 99%